Residential Radon Exposure and Skin Cancer Incidence in a Prospective Danish Cohort - Bräuner, Elvira Vaclavik (PLoS One, 2015)
BACKGROUND: Although exposure to UV radiation is the major risk factor for skin cancer, theoretical models suggest that radon exposure can contribute to risk, and this is supported by ecological studies. We sought to confirm or refute an association between long-term exposure to residential radon and the risk for malignant melanoma (MM) and non-melanoma skin cancer (NMSC) using a prospective cohort design and long-term residential radon exposure. METHODS: During 1993–1997, we recruited 57,053 Danish persons and collected baseline information. We traced and geocoded all residential addresses of the cohort members and calculated radon concentrations at each address lived in from 1 January 1971 until censor date. Cox proportional hazards models were used to estimate incidence rate-ratios (IRR) and confidence intervals (CI) for the risk associated with radon exposure for NMSC and MM, and effect modification was assessed. RESULTS: Over a mean follow-up of 13.6 years of 51,445 subjects, there were 3,243 cases of basal cell carcinoma (BCC), 317 cases of squamous cell carcinoma (SCC) and 329 cases of MM. The adjusted IRRs per 100 Bq/m(3) increase in residential radon levels for BCC, SCC and MM were 1.14 (95% CI: 1.03, 1.27), 0.90 (95% CI: 0.70, 1.37) and 1.08 (95% CI: 0.77, 1.50), respectively. The association between radon exposure and BCC was stronger among those with higher socio-economic status and those living in apartments at enrollment. CONCLUSION AND IMPACT: Long-term residential radon exposure may contribute to development of basal cell carcinoma of the skin. We cannot exclude confounding from sunlight and cannot conclude on causality, as the relationship was stronger amongst persons living in apartments and non-existent amongst those living in single detached homes.